Uncertainty and Inducements to Invest - Hart, Albert Gailord (Review of Economic Studies, 1940)
Journal Article Uncertainty and Inducements to Invest Get access Albert Gailord Hart Albert Gailord Hart Ames, Iowa, U.S.A. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 8, Issue 1, October 1940, Pages 49–53, https://doi.org/10.2307/2967417 Published: 01 October 1940